The governance of standard setting and the role of academia in Italian accounting regulation, 1942 to the present. (August 2019) - Quagli, Alberto; Avallone, Francesco; Ramassa, Paola; Roncagliolo, Elisa
This article provides a historical analysis of the role of the accounting academia in influencing Italian accounting regulation from the 1942 Civil Code to the present. It builds on the theory of social order to investigate the evolution of accounting regulation in accordance with the rise, dominance, and decline of the sources of social order and finds that academia has progressively lost its influence. The declining role of academia is interpreted in light of its inability to evolve from a vibrant community to a more structured association, which contributed to the lack of a unified position and of a formally acknowledged representation in the Italian standard setter. The progressive exclusion of academics also parallels the growing role of professional associations in the increasingly structured governance of standard setting. Moreover, this work highlights a progressive fading of the typical features of community and the collective identity originally characterizing Italian accounting academia.